Ethical leadership in organizations: a review of the literature (2018)
This article identifies the research trends on ethical leadership in organizations and the theoretical gaps that may constitute future lines of study. The bibliographical review is supported by IT tools, such as the Tree of Science, designed to provide support for the documentary search. These trends are classified as: 1) Individual aspects (traits, personal values, leadership style); 2) group aspects (leader-follower exchange, effects on followers); 3) organizational aspects (organizational culture, internal stakeholders) and 4) contextual aspects (national cultures, external stakeholders). It concludes that the research on ethical leadership has been focused on the leader-followers’ interactions and the effects of such interaction. In minor measure, it has been studied the individual and organizational analysis level. The contextual level has been the least researched.